2009
DOI: 10.1097/jcp.0b013e3181a45ed0
|View full text |Cite
|
Sign up to set email alerts
|

Association of Posttraumatic Stress Disorder With Increased Prevalence of Metabolic Syndrome

Abstract: Objective Few studies have compared prevalence rates of metabolic abnormalities in antipsychotic-treated patients with different psychiatric disorders, including posttraumatic stress disorder (PTSD). In this study, we examined components of metabolic syndrome among middle-aged and older patients with psychiatric disorders. Method In the study, 203 outpatients older than 40 years and with psychotic symptoms that needed antipsychotic treatment were enrolled. Among them, 65 had a diagnosis of schizophrenia, 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 48 publications
2
34
0
1
Order By: Relevance
“…Compared to the previous physical health conditions, L'Aquila population showed an increase in the body mass index higher levels of blood pressure and an increase in thyroid pathologies (Mollica et al 2011), and a higher prevalence of metabolic syndrome, confirming the literature results (Jin et al 2009;Weiss et al 2011).…”
Section: The Cooperation With General Practitioners (Gps)supporting
confidence: 80%
“…Compared to the previous physical health conditions, L'Aquila population showed an increase in the body mass index higher levels of blood pressure and an increase in thyroid pathologies (Mollica et al 2011), and a higher prevalence of metabolic syndrome, confirming the literature results (Jin et al 2009;Weiss et al 2011).…”
Section: The Cooperation With General Practitioners (Gps)supporting
confidence: 80%
“…Our search yielded 752 publications of which nine [27][28][29][30][31][32][33][34][35] [Insert Figure 1 about here]…”
Section: Search Results and Included Participantsmentioning
confidence: 99%
“…Three studies [28,32,35] reported on obesity frequency defined as waist circumference (>102cm in males and >88cm in females (ATP-III or ATP-III-A), while none of the studies reported the obesity frequency following the ethnicityspecific IDF-criteria. Overall, the proportion of people with PTSD with abdominal obesity by the ATP definitions was 49.3% (n=194; 95%CI=29.7%-69.0%; Q=14.8, p<0.001).…”
Section: Individual Metabolic Abnormalities Among People With Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Finally, posttraumatic stress disorder (PTSD) is associated with poor physical health outcomes, including obesity, metabolic syndrome, and cardiovascular disease. [29][30][31] There is a lack of prospective research examining sleep and physical activity in PTSD, and disentangling these relationships could serve as a first step to developing targeted behavioral interventions to prevent morbidity and mortality in PTSD. In the current study, we assessed the relationship between sleep quality at baseline and physical activity one year later in individuals with and without PTSD.…”
mentioning
confidence: 99%